2008
DOI: 10.1073/pnas.0801965105
|View full text |Cite
|
Sign up to set email alerts
|

Flow induces loop-to-β-hairpin transition on the β-switch of platelet glycoprotein Ibα

Abstract: Interaction of glycoprotein Ib␣ (GPIb␣) with von Willebrand factor (VWF) initiates platelet adhesion to injured vascular wall to stop bleeding. A major contact between GPIb␣ and VWF involves the ␤-switch region, which is a loop in the unliganded GPIb␣ but switches to a ␤-hairpin in the complex structure. Paradoxically, flow enhances rather than impedes GPIb␣-VWF binding. Gain-offunction mutations (e.g., M239V) in the ␤-switch reduce the flow requirement for VWF binding, whereas loss-of-function mutations (e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
47
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 27 publications
2
47
0
Order By: Relevance
“…For example, the instability of GPIba b-hairpin without vWF is demonstrated by a free MDS as a spontaneous transition to a structureless loop. 59 But for vWF-A1/GPIba complex, MDS exhibits its conformational flexibility and the stabilizing electrostatic interactions between these two proteins. 40 The unfolding of the central b-sheet of vWF-A2 is proposed to start from its edges and then propagate into its center.…”
Section: Molecular Dynamic Simulation Of Molecular Biomechanicsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the instability of GPIba b-hairpin without vWF is demonstrated by a free MDS as a spontaneous transition to a structureless loop. 59 But for vWF-A1/GPIba complex, MDS exhibits its conformational flexibility and the stabilizing electrostatic interactions between these two proteins. 40 The unfolding of the central b-sheet of vWF-A2 is proposed to start from its edges and then propagate into its center.…”
Section: Molecular Dynamic Simulation Of Molecular Biomechanicsmentioning
confidence: 99%
“…55 SMD simulations on unbinding of receptor from its ligand, such as P-selectin glycoprotein ligand 1 (PSGL-1) from P-selectin and glycoprotein Iba (GPIba) from vWF-A1, have provided insights into the molecular mechanism underlying catch-bond. 32,40,58,103 Flow MDS was inspired from FC assay and first carried out by Lou and Zhu 59 and further improved by Chen et al…”
Section: Molecular Dynamic Simulation Of Molecular Biomechanicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a number of investigations have shown that the single bond between the GP Ib-IX complex and vWf cannot be maintained under high shear force imposed on either platelets or the GP Ib-IX-expressing CHOs. In addition, vWf is a large multimeric molecule possessing multiple sites that can interact with GP Ib␣; therefore, GP Ib-IX complexes could be clustering on vWf, which allows for resistance to the shear force through the anchorage of the GP Ib-IX complex to the platelet cytoskeleton (3)(4)(5). Along this line, a GEM-based localization to concentrate larger numbers of GP Ib␣ molecules should facilitate such multivalent binding.…”
mentioning
confidence: 99%
“…FcR␥ (16) and Fc␥RIIA (17,18)). One of the features of cell membranes is the existence of specialized glycosphingolipidenriched membranes (GEMs), 3 to which not only a number of receptors, in platelets, such as GP Ib-IX complex (19), Fc␥RIIA (19), P 2 X 1 (20), and P 2 Y 12 (21), but also various kinases, phosphatases, and adaptor proteins (22,23) are localized. Therefore, one would expect that upon ligand-receptor interaction, the receptor-associated GEMs can act as a platform or carrier to support a transmembrane signal, as well as the interplay of different signals elicited by various GEM-associated receptor-ligand interactions, helping them bind in an efficient, controlled, and synergistic manner.…”
mentioning
confidence: 99%